THE GENE POOL OF THE ANIMAL SPECIES OF POLTAVA AND RISKS OF LOSS OF LOCAL POPULATIONS - Войтенко, С. Л. (Scientific Progress & Innovations, 2015)
The article presents the results of certification of entities breeding in dairy cattle breeding of Poltava region, and examination of local herds of small animal breeds. It is revealed that breeding farms of breeding cattle of dairy breeds differ both by the level of selection and breeding work, and the number of cows in herds and their performance. A significant number of households does not have an automated system for the maintenance of tribal records, making it impossible for effective selection of animals, assessing them by a number of features and improve performance in a number of generations. Industry analysis confirmed that in the region in the category of subjects of dairy cattle’s breeding are households where there are significant violations with the reproduction of the herd, unreasonable use of certain sires, the high cost of feed for milk production. It was offered to carry out the selection in herds in accordance with programmes with specific breeds under the control of academic institutions. Examination of herds of local breeds in Poltava region, among which Mirgorod breed of pigs, Sokolska breed of sheep and Poltava clay colour breed of hens showed their critical condition by the number of permanent declining of populations as a result of lack of demand for livestock products. The conservation of these populations is impossible without government subsidies, and their disappearance is correlative loss of national heritage and cultural values.